Heparin Neutralizing Activity in Patients with Renal Disease on Maintenance Haemodialysis - Aronstam, A; Dennis, B; Friesen, M J; Clark, W F; Linton, A L; Lindsay, R M (Thrombosis and Haemostasis, 1978)
Heparin neutralizing activity (HNA) was increased in plasma of patients with end-stage renal disease treated by maintenance haemodialysis. It was not raised in non-dialyzed patients with chronic renal failure, nor in patients with normal renal function who had been exposed to the extracorporeal circulation of the heart-lung bypass 48–72 hr before testing. It is postulated that the trauma of extracorporeal circulation causes platelets to release HNA which is not cleared by the dialysis membranes of the artificial kidney but is by the human kidney. This may have therapeutic implications for heparin dosage schedules during haemodialysis.